(untitled) (International Journal on Stereo & Immersive Media, 2021)
The Modern Marvel Company was incorporated in Edinburgh in 1897, with a remit to educate and entertainment. Building on the wider popularisation of science and radical changes in pedagogy, the company exploited various optical technologies to fulfil an ideal of universal education. The cinematograph and the Analyticon regularly shared the same bill; the latter was a stereoscopic technology built upon the principle of polarised light that depended upon a silver screen to work. Within the context of Edinburgh, stereoscopy directed shaped the ideological and aesthetic character of early cinema. This paper adopts tropes of traditional technological history by detailing the Analyticon’s technical workings, but it also adopts the principles of New Cinema History by situating this technology within a nuanced social context. In doing so, this paper offers a fuller understanding of early cinema’s aesthetic, social and cultural significance in Edinburgh, and its relationship with the wider visual culture of the 1890s.